Factors Related to Outpatient Pharmacy Service Waiting Time at Hermina Daan Mogot Hospital In 2022 - Aisyah, Siti; Angelina Kusumaningtiar, Devi; Azteria, Veza; Veronika, Erna (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: The long waiting time for service is a potential problem that always has an impact on patient complaints in several health care facilities.  Objective: This study aims to determine the factors related to waiting time for Outpatient Pharmacy services at Hermina Daan Mogot Hospital in 2022. Method: This type of research is quantitative with a cross-sectional study design. Data collection used secondary data obtained for 1 week retrospectively through the PASHMINA application using a form. Result and Discussion: The results showed that 69.3% of the waiting time for pharmaceutical services was inappropriate,60.6% finished drug prescriptions,51.9% <3items and 53.8% used BPJS payment. The results of the Chi square test showed that there was a relationship between the type of prescription (p-value=0.004, PR=1.709), number of drug items (p-value=0.0001, PR=3.023), payment status (p-value 0.0001) and waiting time for pharmaceutical services.  Conclusion: The author suggests that the Management of Hermina Daan Mogot Hospital make efforts to improve by minimizing the number of concoction prescriptions, monitoring the number of drug items, developing SIMRS, commitment to discipline in drug prescribing and setting the pharmacy staff's official schedule more optimally